2012
DOI: 10.1038/nphys2434
|View full text |Cite
|
Sign up to set email alerts
|

Self-organized electromagnetic field structures in laser-produced counter-streaming plasmas

Abstract: Self-organization 1,2 occurs in plasmas when energy progressively transfers from smaller to larger scales in an inverse cascade 3 . Global structures that emerge from turbulent plasmas can be found in the laboratory 4 and in astrophysical settings; for example, the cosmic magnetic field 5,6 , collisionless shocks in supernova remnants 7 and the internal structures of newly formed stars known as Herbig-Haro objects 8 . Here we show that large, stable electromagnetic field structures can also arise within counte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
108
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(111 citation statements)
references
References 28 publications
2
108
0
1
Order By: Relevance
“…The beam foci had a minor diameter of 900 µm, and used distributed phase-plate (DPP) beam smoothing, for ontarget laser intensities near 5 × 10 13 W/cm 2 . The laser setup was similar to the recent interacting plume experiments of Kugland et al [19], which observed large-scale "self-organized" plasma structures, except for smaller separation of the targets and the use of broader laser foci and DPP phase plate beam smoothing, which may limit the density and decrease the magnitude of self-generated magnetic fields.The electromagnetic fields formed in the interaction region were probed using an ultrafast diagnostic proton beam [17], generated with a third, high-intensity laser …”
mentioning
confidence: 88%
See 1 more Smart Citation
“…The beam foci had a minor diameter of 900 µm, and used distributed phase-plate (DPP) beam smoothing, for ontarget laser intensities near 5 × 10 13 W/cm 2 . The laser setup was similar to the recent interacting plume experiments of Kugland et al [19], which observed large-scale "self-organized" plasma structures, except for smaller separation of the targets and the use of broader laser foci and DPP phase plate beam smoothing, which may limit the density and decrease the magnitude of self-generated magnetic fields.The electromagnetic fields formed in the interaction region were probed using an ultrafast diagnostic proton beam [17], generated with a third, high-intensity laser …”
mentioning
confidence: 88%
“…The first image, at t = 3.8 ns relative to the start of the driver pulse, shows a prominent and sharp"X"-like structure at the midplane, with the protons deflected into pairs of thin lines, reminiscent of the caustic proton structures observed in experiments in a similar laser-energy regime with larger initial target separation [19,20]. However, for the present discussion, we focus on the filamentary instability visible above the "X" structure.…”
mentioning
confidence: 99%
“…Related studies include counter-streaming laser-produced plasmas supporting hohlraum design for indirect-drive inertial confinement fusion [17][18][19] and for studying astrophysically relevant shocks, [20][21][22][23][24] colliding plasmas using wire-array Z pinches, 25,26 and applications such as pulsed laser deposition 27 and laser-induced breakdown spectroscopy. 28 Primary issues of interest in these studies include the identification of shock formation, the formation of a stagnation layer [29][30][31] between colliding plasmas, and the possible role of two-fluid and kinetic effects on plasma interpenetration.…”
Section: Introductionmentioning
confidence: 99%
“…The structure of the reconnection layer in these conditions is unknown, but is expected to adjust to accommodate the rate of magnetic flux delivered into the layer, where, for example, a pileup of the magnetic flux could contribute to controlling the reconnection rate [5,6]. A number of recent laser-driven, high energy density physics (HEDP) experiments [7][8][9][10] have investigated magnetic reconnection in the strongly driven regime, as well as the formation of astrophysically relevant collisionless shocks [11] and self-organized field structures [12]. Large-scale field structures produced by collisions between laser-driven plasma flows have, for example, been interpreted [11] as being due to the accumulation of advected toroidal magnetic fields generated via the Biermann battery mechanism at the laser spots [13].…”
mentioning
confidence: 99%